Monitoring training in elite springboard divers - Minganti, C.; Meeusen, R.; Capranica, L.; de Pero, R.; Piacentini, M. F. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Monitoring training is critical to the process of quantifying and correctly planning training, especially in the periodization of elite athletes. Session RPE method has proven to be successful in monitoring training load during steady state, high-intensity and multiple types of exercises (Foster C.,`96, `98, 2001, Minganti C. 2008). Divers practice basic skills, basic dives and optional dives from different heights (both springboard and platform); dryland workouts are also scheduled to work on specific skills and to improve strength and flexibility. No previous studies were conducted to evaluate the session RPE method in this sport Therefore, the aim of the present study was to evaluate the ability of the session RPE method to quantify training during diving practice. Methods: Six elite divers, three males (age=25,7±6,1yrs; height= 171±6,1 cm; weight=66,7±1,2 kg) and three females (age=25,3±1yrs; height= 163,3 ±4,7 cm; weight=58,3±4 kg) participated in the present study. Each subject was monitored during two different training sessions (1 and 3 meters springboard) with a Heart Rate (HR) monitor (Polar Team System), and the RPE rating was obtained using the 10 cm VAS (Visual Analogue Scale). The subjects were asked to provide a rating of the overall difficulty of the training session 30 minutes after the end of the session. An exercise score for each training session was computed by multiplying the duration of the training session by the RPE (Session RPE). As an objective reference method for quantifying each training session the summated HR zone method (Edwards S.,`93) was used. The HR monitors were downloaded using software that allowed evaluation of the accumulated time in each of 5 HR zones based on 50-60%, 60-70%, 70-80%, 80-90% and 90-100% of theoretical HR peak (220-age). Time in each zone was used to calculate the training score (TRIMP) by multiplying the accumulated duration in each HR zone by different factors (50-60%=1; 60-70%=2; 70-80%=3; 80-90%=4, 90-100%=5) and summating the Results: Results: Pearson`s correlation coefficient was used to evaluate the relationship between TRIMP scores (TRIMP =96±18,18) generated using the summated HR zone method and the session RPE (Session RPE =2372±882,28) method of monitoring the training session. Results (r= 0,88; p<0,05) shows a high correlation coefficient between the two Methods: Discussion: Results of this study are consistent with previous observations of a strong correlation between session RPE and the summated HR zones methods of evaluating training sessions. Our results suggest that the session RPE method may be used as an easy method of creating a TRIMP score for evaluating exercise training in diving as well.